Mobile Forensics in Human Trafficking Investigation Services Using Mobile Laboratory - Muammar Muammar; Imam Riadi; Rusydi Umar (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
This research examines the application of a mobile digital forensic laboratory developed by the Digital Forensics Center (DFC) at UMP to handle digital evidence directly at crime scenes, specifically in human trafficking cases. Integrating the Association of Chief Police Officers' (ACPO) methods, this mobile lab facilitates the investigative process, from planning to evidence collection and analysis, without delaying transport to a central lab, thereby speeding response times and minimizing evidence degradation.Â We employed Magnet Axiom and DF-Tools to analyze WhatsApp data. Each demonstrated varying performance in identifying key digital evidence such as text messages, media, and group chats. DF-Tools showed an advantage in identifying multimedia artifacts with a 69.48% data acquisition success rate, compared to Magnet Axiom at 68.57%. Additionally, police bolstered their efforts to uncover human trafficking networks by implementing Base Transceiver Station (BTS)-based location tracking techniques to pinpoint suspect and victim locations via phone data or identity numbers. The research findings demonstrate that mobile labs enable rapid on-site responses, offer flexibility in collecting and securing digital evidence, and enhance efficiency and effectiveness of digital forensic investigations.